Surface adhesins and exopolymers of selected foodborne pathogens - Jaglic, Zoran (2014)
The ability of bacteria to bind different compounds and to adhere to biotic and abiotic surfaces provides them with a range of advantages, such as colonization of various tissues, internalisation, avoidance of an immune response and survival and persistence in the environment. A variety of bacterial surface structures are involved in this process and these promote bacterial adhesion in a more or less specific manner. In this review, we will focus on those surface adhesins and exopolymers in selected foodborne pathogens that are involved mainly in primary adhesion. Their role in biofilm development will also be considered when appropriate. Both the clinical impact and implications for food safety of such adhesion will be discussed.